Light demand characteristics, production performance, and changes in the feeding patterns of broilers - Wang, Shouyi; Jiang, Guoping; Pan, Chenghao; Santos, Thebano; Elhadidi, Yasser; Jado, Ahmed; Jin, Shufang; Pan, Jinming (International Journal of Agricultural and Biological Engineering, 2024)
Poultry is a light-sensitive animal and the light environment has an important influence on the growth anddevelopment of these animals. Previous studies have mainly focused on the effects of the light environment on variousphysiological indicators of poultry but seldom explored the light demand characteristics of broilers under free selection. Thisexperiment mainly studied the light demand characteristics of broilers under a yellow LED light environment and the influenceof different breeding densities [low-density (2.5 broilers/m2), high-density (7.5 broilers/m2)] on the production performance anddiet characteristics of broilers. Studies showed that the production performance indexes of low-density groups are higher thanthose of high-density groups. The feed and water consumption in the light area of the two experimental groups weresignificantly higher than those in the dark area, which means that the broilers showed a great preference for the light area.However, as the age of the broilers increased, the food and water consumption of the broilers decreased, indicating that broilershad a lower preference for light in the middle and late stages of growth. The statistical results for the residence frequencydistribution characteristics showed that broiler chickens had different light requirements at different growth stages under thecondition of active selection: 1) low-density breeding environment: 23.8L (light):0.2D (dark) for chicks and 22.3L:1.7D foradult broilers; 2) high-density breeding environment: 22.6L:1.4D for chicks and 15.0L:9.0D for adult broilers. This study willprovide a reference for the optimization and control of light environment in broiler breedingKeywords: broiler, light-demand characteristics, production performance, feeding patternDOI: 10.25165/j.ijabe.20241702.7411Citation: Wang S Y, Jiang G P, Pan C H, Santos T, Elhadidi Y, Jado A, et al. Light demand characteristics, productionperformance, and changes in the feeding patterns of broilers. Int J Agric & Biol Eng, 2024; 17(2): 68–73